2013
DOI: 10.17711/sm.0185-3325.2013.053
|View full text |Cite
|
Sign up to set email alerts
|

Incremento de la temperatura ambiental y su posible asociación al suicidio en Baja California Sur (BCS) 1985-2008

Abstract: Introducción. Durante las últimas décadas se ha podido apreciar un cambio en las variables climáticas, en especial en la temperatura ambiental. Hay evidencias que asocian el aumento de la temperatura ambiental con el incremento en las tasas de mortalidad por suicidio. Objetivo. Evaluar la relación entre la tasa de suicidio y la temperatura ambiental en Baja California Sur (BCS) durante los años 1985-2008. Método. Los datos de suicidio fueron obtenidos de las bases de Mortalidad del INEGI de 1985-2008. Se tabul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
2
0
2
Order By: Relevance
“…In spite of the limitations, to the best of our knowledge only one other study has reported on the relationship between climate and suicides in Mexico, and that was limited to one state in the country [ 78 ]. Considering the nature of the phenomenon, a strength of this work is the presentation of the wavelet analysis as a suitable option because of its usefulness in analyzing long time series, especially when mathematical properties change over time.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the limitations, to the best of our knowledge only one other study has reported on the relationship between climate and suicides in Mexico, and that was limited to one state in the country [ 78 ]. Considering the nature of the phenomenon, a strength of this work is the presentation of the wavelet analysis as a suitable option because of its usefulness in analyzing long time series, especially when mathematical properties change over time.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the findings of Fernández-Niño et al (2016), who found that May was the month with the highest frequency of suicides in Mexico from 2000 to 2013. A recent study analyzed the behavior of suicide in the state of Baja California Sur from 1985 to 2008, observing a sharp increase in suicide rates during the hot season (months with an average temperature of over 30°C), together with an association between temperature and suicide rates (Gaxiola-Robles, Celis de la Rosa, Labrada-Martagón, Díaz-Castro, & Zenteno-Savín, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…(15,16,5,7). También, se ha documentado que el incremento de la temperatura ambiental puede ser causal de suicidio (17). Los resultados mostraron que hay una asociación entre las temperaturas ambientales y las afectaciones a la salud, y aunque no se puede demostrar una causalidad con la regresión de Poisson, la literatura indica que hay un efecto de las temperaturas ambientales sobre diversos aspectos de la salud (15,17,14).…”
Section: Discusión Temperaturas Ambientales Y La Salud De Los Hidalgu...unclassified
“…También, se ha documentado que el incremento de la temperatura ambiental puede ser causal de suicidio (17). Los resultados mostraron que hay una asociación entre las temperaturas ambientales y las afectaciones a la salud, y aunque no se puede demostrar una causalidad con la regresión de Poisson, la literatura indica que hay un efecto de las temperaturas ambientales sobre diversos aspectos de la salud (15,17,14). De esta manera, la tendencia de aumento de la temperatura ambiental (máxima mensual, promedio mensual, y mínima mensual) que se registró en el estado de Hidalgo, sugiere modificaciones en el patrón de afecciones a la salud, incrementando los casos de deshidratación, agotamiento y golpes de calor.…”
Section: Discusión Temperaturas Ambientales Y La Salud De Los Hidalgu...unclassified